Synergy-Acmeological Model Modern Lesson in the System of Literary Education - Svitlana Piroshenko (Pedagogical Discourse, 2014)
This article presents a theoretical model of student co-reader, and a teacher of literature in the area of modern class-based competency-activity technology education. Attention is focused on the conceptual and terminological toolkit on the designated topic, it will liquidate most cases, the conclusions and integrate potential accumulated in the construction of the school literary education and teaching methods.According to the author, literature lesson should be built so that everyone can systematically train and gain fluency in defined ways of his own, a set of competencies that demonstrate professional and methodical and literary reader's level teacher. Built system of the teacher and student of literature, the reader should be on a new relationship, which appear to be a work of art, literary and artistic materials and communications.Researcher reviewed literature class concept, based on the process of learning to be done on the basis fasylitatyvniy in the context of synergy-aksiolohiko-acmeological plane.